Clay-based electrothermal composite film for directly trapping CO2 in air, preparation method and application
Through the design of clay-based electrothermal composite film and combined with the electric heating assisted regeneration mechanism, the problems of high energy consumption and poor material stability in the existing technology are solved, and high-efficiency and low-energy consumption CO2 capture and adsorbent regeneration are achieved.
Patent Information
- Application Number
- CN202510165004.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-02-14
AI Technical Summary
The existing direct air capture technology has many challenges in energy consumption, cost and material stability, and traditional adsorbent materials are difficult to achieve large-scale application in terms of humidity influence and high regeneration energy consumption.
Using clay-based electrothermal composite film, by combining one-dimensional clay nanofibers with polyethyleneimine and introducing carbon nanomaterials, combined with an electric heating-assisted regeneration mechanism, the adsorption capacity and selectivity of CO2 are improved and the regeneration energy consumption is reduced.
It realizes high-efficiency, low-energy consumption CO2 capture and adsorbent regeneration, improves the CO2 adsorption performance and regeneration efficiency of the material, and maintains stable performance after multiple regeneration cycles.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon capture, and relates to a clay-based electrothermal composite membrane for directly capturing CO2 in the air, a preparation method and an application thereof. Background Art
[0002] With the acceleration of industrialization and the increasing severity of global climate change, reducing greenhouse gas emissions, especially carbon dioxide (CO2) emissions, has become a major challenge faced by the international community. Direct Air Capture (DAC) technology, as a potential solution, is expected to provide important support for achieving carbon neutrality goals by directly separating and capturing CO2 from the atmosphere. However, existing DAC technology still faces many challenges in terms of energy consumption, cost and material stability.
[0003] At present, direct air capture technology mainly relies on liquid adsorbents or solid adsorbents to achieve CO2 capture. However, these methods often have problems such as limited adsorption capacity, difficult regeneration, and high energy consumption. In addition, although traditional adsorbent materials such as activated carbon and molecular sieves have certain capture capabilities, they are easily affected by humidity in practical applications, and the regeneration process has high energy consumption, which limits their large-scale application.
[0004] Clay minerals, as a type of silicate minerals with a unique layered structure, show broad application prospects in the field of environmental governance due to their good adsorption properties, ion exchange capacity and stability. However, the application of single clay materials in direct air capture is limited by their low CO2 selectivity and adsorption capacity, as well as possible thermal stability problems during the regeneration process. Therefore, how to improve the CO2 capture performance and regeneration efficiency of clay-based materials through modification or composite means has become an important direction of current research.
[0005] At present, the regeneration of solid amine adsorbents usually includes temperature swing adsorption (TSA), pressure swing adsorption (PSA), vacuum swing adsorption (VSA) or a combination of the above methods. For direct air capture, Rahimi et al. pointed out in the Bench-scale demonstration of CO2 capture with an electrochemically driven proton concentration process that the use of PSA technology consumes a lot of energy on non-target gases such as compressed nitrogen and oxygen. In TSA technology, the heat input mainly acts on the solid and has no obvious correlation with the CO2 source concentration. Therefore, a better method is needed to reduce the regeneration energy consumption of the adsorbent. In the process of exploring the performance optimization of clay-based adsorbents, by introducing carbon nanomaterials (such as carbon nanotubes, graphene, etc.), the materials are given electrothermal and photothermal synergistic properties, which significantly improves its regeneration efficiency and reduces energy consumption. Specifically, the high conductivity and photothermal conversion ability of carbon nanomaterials enable the adsorbent to achieve rapid heating through electrical heating or solar irradiation, thereby reducing the external energy input required for traditional thermal regeneration.
[0006] In view of the shortcomings of the prior art, the present invention proposes a clay-based electrothermal composite membrane for direct air capture of CO2 and a preparation method thereof. The composite membrane combines the natural advantages of clay minerals with modern electrothermal technology, and aims to achieve high-efficiency, low-energy CO2 capture and adsorbent regeneration by optimizing material composition and structural design. Summary of the invention
[0007] The purpose of the present invention is to provide an efficient, stable and easily regenerated clay-based electrothermal composite membrane material and a simple and easy preparation method thereof, aiming to provide a new material selection and technical solution for direct air capture technology, thereby promoting the development and application of CO2 emission reduction technology, which is of great significance for alleviating global climate change. At the same time, the present invention also explores the influence of different factors on the performance of the composite membrane, providing a theoretical basis and practical guidance for further optimizing the performance of the material.
[0008] The technical solution of the present invention:
[0009] A method for preparing a clay-based electrothermal composite membrane for directly capturing CO2 in the air comprises the following steps:
[0010] S1. Preparation of one-dimensional clay nanofiber dispersion:
[0011] The one-dimensional clay material is mixed with deionized water to prepare a mixed aqueous solution with a mass-volume concentration of 10 to 30 g / L to obtain a one-dimensional clay mixed solution; the one-dimensional clay mixed solution is subjected to ultrasonic dispersion treatment to obtain a one-dimensional clay nanofiber dispersion solution;
[0012] S2. Preparation of polymer solution:
[0013] The polymer was mixed with deionized water, and the mixture was heated in an oil bath at 70° C., and magnetically stirred at 500 rpm for 2 hours to completely dissolve the polymer in the deionized water, thereby preparing a polymer solution with a mass-volume concentration of 10 to 50 g / L;
[0014] S3, preparing polyethyleneimine composite slurry:
[0015] The carbon nanomaterial is mixed with a one-dimensional clay nanofiber dispersion to prepare a mixed solution 1 of carbon material and clay fiber with a mass-volume concentration of 15 to 50 g / L, and the mixed solution 1 is subjected to ultrasonic dispersion treatment to uniformly disperse the carbon nanomaterial in the dispersion; a polymer solution is added to the mixed solution 1, and the mass of the polymer in the polymer solution accounts for 5 to 15 wt% of the solid content in the mixed solution 1 of the carbon material and clay fiber to obtain a carbon material clay polymer mixed dispersion 2; a polyethyleneimine solution with a concentration of 100 g / L is added to the carbon material clay polymer mixed dispersion 2, and the mass of the polyethyleneimine in the polyethyleneimine solution accounts for 10 to 50 wt% of the solid content in the carbon material clay polymer mixed dispersion 2; the carbon material clay polymer mixed dispersion 2 after adding the polyethyleneimine is magnetically stirred at a speed of 300 rpm for 10 minutes, and subjected to bath ultrasonication for 10 minutes to obtain a uniformly mixed polyethyleneimine composite slurry;
[0016] S4, Heating Assisted Evaporation Film Forming:
[0017] The polyethyleneimine composite slurry obtained in step S3 is assisted to evaporate at a temperature of 40° C. to 60° C. for 6 to 12 hours to obtain a clay-based electrothermal composite membrane for directly capturing CO2 in the air.
[0018] The ultrasonic dispersion treatment is carried out by using a tip ultrasonic treatment; in step S1, the ultrasonic treatment time is 30 to 60 minutes; in step S3, the ultrasonic treatment time is 10 to 30 minutes.
[0019] The one-dimensional clay material is sepiolite or palygorskite.
[0020] The carbon material is multi-walled carbon nanotube, carbon black or graphite powder.
[0021] The polymer solution is a polyvinyl alcohol solution, a chitosan solution, a gelatin solution or a xanthan gum solution.
[0022] The beneficial effects of the present invention are as follows: the present invention significantly improves the adsorption capacity and selectivity of the composite membrane for CO2 by compounding one-dimensional clay nanofibers with polyethyleneimine (PEI); the composite membrane of the present invention adopts an electrothermal assisted regeneration mechanism, and can achieve rapid desorption and regeneration at a relatively low energy consumption; all raw materials used are non-toxic or low-toxic substances, and no harmful by-products are produced during the preparation process, which complies with the principles of green chemistry; in addition to CO2 capture, the composite membrane of the present invention also has certain antibacterial and anti-pollution properties, and can be applied to multiple fields such as air purification and water treatment, showing broad application prospects. DETAILED DESCRIPTION
[0023] The specific implementation of the present invention is further described below in conjunction with the technical solution.
[0024] The design concept of the present invention is as follows: the present invention uses ultrasonic dispersion technology to evenly disperse a one-dimensional clay material with a high specific surface area in deionized water to provide a basic skeleton for the subsequent composite membrane. The carbon nanomaterial is mixed with a one-dimensional clay nanofiber dispersion liquid, and the carbon nanomaterial is evenly dispersed by ultrasonic dispersion; then a high molecular polymer solution is added to adjust the polymer content to optimize the performance of the composite membrane; finally, a polyethyleneimine solution is added to further improve the CO2 adsorption capacity and stability of the composite membrane.
[0025] The clay-based electrothermal composite membrane prepared by the present invention has the following characteristics: CO2 adsorption performance is 1.52-2.34 mmol / g, the thermal equilibrium temperature after applying 30V voltage at both ends of the composite membrane is 95-105°C, and the thermal equilibrium temperature under the irradiation of one sun is 82-90°C, both of which can realize regeneration and desorption of the adsorbent, reducing the regeneration energy consumption. After 5 regeneration cycles, the adsorption performance of the composite membrane does not change significantly.
[0026] In the following embodiments, the one-dimensional clay material is sepiolite as an example, but not limited thereto; the carbon nanomaterial is multi-walled carbon nanotube as an example, but not limited thereto; and the polymer solution is polyvinyl alcohol solution as an example, but not limited thereto.
[0027] Embodiment 1:
[0028] A method for preparing a clay-based electrothermal composite membrane for directly capturing CO2 in the air comprises the following steps:
[0029] S1. Preparation of sepiolite nanofiber dispersion:
[0030] The sepiolite is mixed with deionized water to prepare a mixed aqueous solution with a mass-volume concentration of 10 g / L to obtain a one-dimensional clay mixed solution; the one-dimensional clay mixed solution is subjected to ultrasonic dispersion treatment to obtain a one-dimensional clay nanofiber dispersion solution;
[0031] S2, preparing a polyvinyl alcohol solution, comprising the following steps:
[0032] The high molecular polymer was mixed with deionized water, the mixture was heated in an oil bath at 70°C, and magnetically stirred at 500 rpm for 2 hours to completely dissolve the polyvinyl alcohol in the deionized water phase to prepare a polyvinyl alcohol solution with a mass-volume concentration of 50 g / L.
[0033] S3, preparing polyethyleneimine composite slurry:
[0034] The multi-walled carbon nanotubes and the sepiolite dispersion are mixed to prepare a carbon tube and sepiolite fiber mixed solution 1 with a mass-volume concentration of 15 g / L, and the mixed solution 1 is subjected to ultrasonic dispersion treatment to uniformly disperse the carbon nanomaterial therein; a high molecular polymer solution is added to the mixed solution 1, and the mass of the polymer in the polymer solution accounts for 10wt% of the solid content in the carbon material and clay mixed solution, so as to obtain a carbon material clay polymer mixed dispersion 2; a polyethyleneimine solution with a concentration of 100 g / L is added to the mixed dispersion 2, and the mass of the polyethyleneimine in the polyethyleneimine solution accounts for 10wt% of the solid content in the mixed solution 2, and the carbon material clay polymer mixed solution 2 is magnetically stirred at a speed of 300 rpm for 10 minutes and subjected to bath ultrasonic treatment for 10 minutes to obtain a uniformly mixed polyethyleneimine composite slurry 3;
[0035] S4, Heating Assisted Evaporation Film Forming:
[0036] The polyethyleneimine composite slurry obtained in step S3 is poured into a container and assisted evaporated at 40° C. for 6 hours to obtain a clay-based electrothermal composite membrane for directly capturing CO 2 in the air.
[0037] It was determined that the CO2 adsorption performance of the clay-based composite membrane obtained in Example 1 was 1.52 mmol / g, the thermal equilibrium temperature was 105°C after applying a voltage of 30V at both ends of the composite membrane, and the thermal equilibrium temperature under sunlight was 82°C, both of which could achieve regeneration and desorption of the adsorbent, reducing the regeneration energy consumption. After 5 regeneration cycles, the adsorption performance of the composite membrane did not change significantly.
[0038] Embodiment 2:
[0039] A method for preparing a clay-based electrothermal composite membrane for directly capturing CO2 in the air comprises the following steps:
[0040] S1. Preparation of sepiolite nanofiber dispersion:
[0041] The sepiolite is mixed with deionized water to prepare a mixed aqueous solution with a mass-volume concentration of 10 g / L to obtain a one-dimensional clay mixed solution; the one-dimensional clay mixed solution is subjected to ultrasonic dispersion treatment to obtain a one-dimensional clay nanofiber dispersion solution;
[0042] S2, preparing a polyvinyl alcohol solution, comprising the following steps:
[0043] The high molecular polymer was mixed with deionized water, the mixture was heated in an oil bath at 70°C, and magnetically stirred at 500 rpm for 2 hours to completely dissolve the polyvinyl alcohol in the deionized water phase to prepare a polyvinyl alcohol solution with a mass-volume concentration of 50 g / L.
[0044] S3, preparing polyethyleneimine composite slurry:
[0045] The multi-walled carbon nanotubes and the sepiolite dispersion are mixed to prepare a carbon tube and sepiolite fiber mixed solution 1 with a mass-volume concentration of 15 g / L, and the mixed solution 1 is subjected to ultrasonic dispersion treatment to uniformly disperse the carbon nanomaterial therein; a high molecular polymer solution is added to the mixed solution 1, and the mass of the polymer in the polymer solution accounts for 10wt% of the solid content in the carbon material and clay mixed solution, so as to obtain a carbon material clay polymer mixed dispersion 2; a polyethyleneimine solution with a concentration of 100 g / L is added to the mixed dispersion 2, and the mass of the polyethyleneimine in the polyethyleneimine solution accounts for 30wt% of the solid content in the mixed solution 2, and the carbon material clay polymer mixed solution 2 is magnetically stirred at a speed of 300 rpm for 10 minutes and subjected to bath ultrasonic treatment for 10 minutes to obtain a uniformly mixed polyethyleneimine composite slurry 3;
[0046] S4, Heating Assisted Evaporation Film Forming:
[0047] The polyethyleneimine composite slurry obtained in step S3 is poured into a container and assisted evaporated at 50° C. for 6 hours to obtain a clay-based electrothermal composite membrane for directly capturing CO 2 in the air.
[0048] It was determined that the CO2 adsorption performance of the clay-based composite membrane obtained in Example 2 was 2.05 mmol / g, the thermal equilibrium temperature was 110°C after applying a voltage of 30V at both ends of the composite membrane, and the thermal equilibrium temperature under sunlight was 85°C, both of which could achieve regeneration and desorption of the adsorbent, reducing the regeneration energy consumption. After 5 regeneration cycles, the adsorption performance of the composite membrane did not change significantly.
[0049] Embodiment 3:
[0050] A method for preparing a clay-based electrothermal composite membrane for directly capturing CO2 in the air comprises the following steps:
[0051] S1. Preparation of sepiolite nanofiber dispersion:
[0052] The sepiolite is mixed with deionized water to prepare a mixed aqueous solution with a mass-volume concentration of 10 g / L to obtain a one-dimensional clay mixed solution; the one-dimensional clay mixed solution is subjected to ultrasonic dispersion treatment to obtain a one-dimensional clay nanofiber dispersion solution;
[0053] S2, preparing a polyvinyl alcohol solution, comprising the following steps:
[0054] The high molecular polymer was mixed with deionized water, the mixture was heated in an oil bath at 70°C, and magnetically stirred at 500 rpm for 2 hours to completely dissolve the polyvinyl alcohol in the deionized water phase to prepare a polyvinyl alcohol solution with a mass-volume concentration of 50 g / L.
[0055] S3, preparing polyethyleneimine composite slurry:
[0056] The multi-walled carbon nanotubes and the sepiolite dispersion are mixed to prepare a carbon tube and sepiolite fiber mixed solution 1 with a mass-volume concentration of 15 g / L, and the mixed solution 1 is subjected to ultrasonic dispersion treatment to uniformly disperse the carbon nanomaterial therein; a high molecular polymer solution is added to the mixed solution 1, and the mass of the polymer in the polymer solution accounts for 10wt% of the solid content in the carbon material and clay mixed solution, so as to obtain a carbon material clay polymer mixed dispersion 2; a polyethyleneimine solution with a concentration of 100 g / L is added to the mixed dispersion 2, and the mass of the polyethyleneimine in the polyethyleneimine solution accounts for 40wt% of the solid content in the mixed solution 2, and the carbon material clay polymer mixed solution 2 is magnetically stirred at a speed of 300 rpm for 10 minutes and subjected to bath ultrasonic treatment for 10 minutes to obtain a uniformly mixed polyethyleneimine composite slurry 3;
[0057] S4, Heating Assisted Evaporation Film Forming:
[0058] The polyethyleneimine composite slurry obtained in step S3 is poured into a container and assisted evaporated at 60° C. for 6 hours to obtain a clay-based electrothermal composite membrane for directly capturing CO 2 in the air.
[0059] The CO2 adsorption performance of the clay-based composite membrane obtained in Example 3 was measured to be 2.34 mmol / g, the thermal equilibrium temperature was 95°C after applying a voltage of 30V at both ends of the composite membrane, and the thermal equilibrium temperature under sunlight was 90°C, both of which could achieve regeneration and desorption of the adsorbent, reducing the regeneration energy consumption. After 5 regeneration cycles, the adsorption performance of the composite membrane did not change significantly.
[0060] The above contents are further detailed descriptions of the present invention in combination with specific preferred technical solutions, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.
Claims
1. A method for preparing a clay-based electrothermal composite membrane for directly capturing CO2 in the air, characterized in that: The following steps are involved: S1. Preparation of one-dimensional clay nanofiber dispersion: The one-dimensional clay material is mixed with deionized water to prepare a mixed aqueous solution with a mass-volume concentration of 10 to 30 g / L to obtain a one-dimensional clay mixed solution; the one-dimensional clay mixed solution is subjected to ultrasonic dispersion treatment to obtain a one-dimensional clay nanofiber dispersion solution; S2. Preparation of polymer solution: The polymer was mixed with deionized water, and the mixture was heated in an oil bath at 70° C., and magnetically stirred at 500 rpm for 2 hours to completely dissolve the polymer in the deionized water, thereby preparing a polymer solution with a mass-volume concentration of 10 to 50 g / L; S3, preparing polyethyleneimine composite slurry: The carbon nanomaterial is mixed with a one-dimensional clay nanofiber dispersion to prepare a mixed solution 1 of carbon material and clay fiber with a mass-volume concentration of 15 to 50 g / L, and the mixed solution 1 is subjected to ultrasonic dispersion treatment to uniformly disperse the carbon nanomaterial in the dispersion; a polymer solution is added to the mixed solution 1, and the mass of the polymer in the polymer solution accounts for 5 to 15 wt% of the solid content in the mixed solution 1 of the carbon material and clay fiber to obtain a carbon material clay polymer mixed dispersion 2; a polyethyleneimine solution with a concentration of 100 g / L is added to the carbon material clay polymer mixed dispersion 2, and the mass of the polyethyleneimine in the polyethyleneimine solution accounts for 10 to 50 wt% of the solid content in the carbon material clay polymer mixed dispersion 2; the carbon material clay polymer mixed dispersion 2 after adding the polyethyleneimine is magnetically stirred at a speed of 300 rpm for 10 minutes, and subjected to bath ultrasonication for 10 minutes to obtain a uniformly mixed polyethyleneimine composite slurry; S4, Heating Assisted Evaporation Film Forming: The polyethyleneimine composite slurry obtained in step S3 is assisted to evaporate at a temperature of 40° C. to 60° C. for 6 to 12 hours to obtain a clay-based electrothermal composite membrane for directly capturing CO2 in the air.
2. The preparation method according to claim 1, characterized in that: The ultrasonic dispersion treatment adopts tip ultrasonic treatment; in step S1, the ultrasonic treatment time is 30 to 60 minutes; in step S3, the ultrasonic treatment time is 10 to 30 minutes.
3. The preparation method according to claim 1, characterized in that: The one-dimensional clay material is sepiolite or palygorskite.
4. The preparation method according to claim 1, characterized in that: The carbon material is multi-walled carbon nanotube, carbon black or graphite powder.
5. The preparation method according to claim 1, characterized in that: The high molecular polymer solution is a polyvinyl alcohol solution, a chitosan solution, a gelatin solution or a xanthan gum solution.
6. A clay-based composite membrane for directly capturing carbon dioxide in the air, prepared according to the preparation method according to any one of claims 1 to 5.
7. Use of the clay-based electrothermal composite membrane for directly capturing carbon dioxide in the air as claimed in claim 6 in carbon dioxide adsorption.
Citation Information
Patent Citations
Sorbent for carbon dioxide reduction from indoor air
CN108579706A
Preparation method and application of CO2 adsorbent
CN111514857A
Chitosan and organic amine composite solid adsorbent for adsorbing carbon dioxide in coal-fired flue gas as well as preparation method, application and regeneration method of chitosan and organic amine composite solid adsorbent
CN115779860A
Preparation and application of direct air trapping carbon dioxide adsorbent with flexibility and electric heating characteristic
CN117258765A
Preparation method and application of carbon dioxide adsorbent particles with high desorption rate
CN120205084A